Effect of High-Temperature Steam Treatment of High-Silica Zeolites of the ZSM-5 Type on Their Acidity and Selectivity of Formation of Lower Olefins from Straight-Run Naphthas; Russian Journal of Applied Chemistry; Vol. 76, iss. 1 - Erofeev V. I. Vladimir Ivanovich (Catalysis, 2003)
Title screen